Care Giver Competency in Prevention Risk of Diabetic Foot Ulcer in Diabetes Mellitus Patients - Kharisma Pratama; Jaka Pradika; Cau Kim Jiu; Gusti Jhoni Putra; Wuriani Wuriani; Usman Usman; Tisa Gusmiah; Yenni Lukita (ABDIMAS: Jurnal Pengabdian Masyarakat, 2021)
Increasing in the incidence of diabetic foot ulcer (DFU) among diabetes mellitus patients (DM), which then access to health services is so far, as well as the lack of knowledge of the local community in preventing and caring for DFU made researchers try to initiate training related to prevention and basic wound care for village health cadres, community leaders, and families family members with DM and at risk for UKD. The activity, which carried out in March 2021, involved the puskesmas in Sui District. Raya, Kab. Kubu Raya. After obtained a permit to carry out activities, the Team briefly contacted the community with the assistance of the Head of RT and RW. Participants who toke part in this activity were those who lived or have a family with diabetes mellitus. Participants were given training related to prevention and treatment of basic wounds, which in the end evaluation followed by publication.